Response of potato to nitrogen and phosphorus fertilizers at Assosa, western Ethiopia. (23rd January 2020) - Setu, Habtam; Mitiku, Tesfaye
Abstract: Low soil fertility is one of the critical factors limiting the productivity of potatoes ( Solanum tuberosum L.) in western Ethiopia. The field experiment was conducted in the 2015 and 2016 cropping seasons to elucidate the response of potato yield, yield components, tuber quality to nitrogen and phosphorus fertilizer, and their economic benefit. The treatment comprised five levels of nitrogen (0, 50, 100, 150, and 200 kg N ha −1 ) and five levels of phosphorus (0, 50, 100, 150, and 200 kg P2 O5 ha −1 ). The experiment was laid out as a randomized complete block design in a factorial (5 × 5) arrangement and we replicated the treatments three times. The results revealed that the interaction of nitrogen and phosphorus did not affect growth, yield, and quality parameters of potato. However, nitrogen alone affected plant height, tuber number per plant, number of stems per hill, and marketable and total tuber yield, but not tuber quality parameters. The optimum yields of both marketable (25.5 Mg ha −1 ) and total (28.4 Mg ha −1 ) tuber yields were observed in the application of 150 kg N ha −1 . Phosphorus treatments had no response for most of the yield, yield components, or tuber quality parameters. Applications of 150 kg N ha −1 provided a maximum gross margin (5138.68 or 141, 773.55 Ethiopian Birr [ETB] ha −1 ) with a 79.4% gross profit margin and the highest benefit‐cost ratio (4.86).